2003
DOI: 10.1021/cm021752q
|View full text |Cite
|
Sign up to set email alerts
|

Control of Powder Microstructure for Improved Infrared Reflectance Modulation of an Electrochromic Plastic Device

Abstract: The so-called plastic technology first developed for Li-ion batteries is demonstrated for its potential optical applications in infrared emissivity control. WO 3 ‚H 2 O powder embedded in a plastic matrix is used as the active component in the LiCoO 2 /Li electrolyte/WO 3 ‚H 2 O system. The role of the microstructure of WO 3 ‚H 2 O as an electrochromic material is investigated. For instance, platelet-shaped grains with a surface area as large as 15 µm 2 induce a large improvement in device contrast properties.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…Not only were these nanotubes made under relatively mild conditions, but their rectangular cross-section morphology was formed by a rolling mechanism with the aid of intercalated polyaniline (PANI). WO 3 ·H 2 O is an excellent candidate for an infrared reflectance-modulation device, [16] all-plastic electrochromic device, and rechargeable Li-ion battery. [17] All WO 3 ·xH 2 O hydrates are built from layers of corner-sharing octahedral units of [WO 6 ] connected by hydrogen bridges of interlayer water molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Not only were these nanotubes made under relatively mild conditions, but their rectangular cross-section morphology was formed by a rolling mechanism with the aid of intercalated polyaniline (PANI). WO 3 ·H 2 O is an excellent candidate for an infrared reflectance-modulation device, [16] all-plastic electrochromic device, and rechargeable Li-ion battery. [17] All WO 3 ·xH 2 O hydrates are built from layers of corner-sharing octahedral units of [WO 6 ] connected by hydrogen bridges of interlayer water molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Evolution of the reflectance spectra beyond the ␣ phase "xÐ0.29… When x is increased from xϭ0.3 to xϭ0.4 ͑see Fig. 6 Over the ␣→␤ and ␤→␥ transitions, the increase of E ⌫ by defect creation may counteract the electron injection resulting in a cancellation of the effects for the reflectance spectra. However, the reflectivity on the longwavelength side slightly decreases, possibly meaning that the electron mobility is reduced.…”
Section: Resultsmentioning
confidence: 99%
“…1 In its crystalline form, WO 3 •H 2 O is able to intercalate Li-ions and to be simultaneously reduced. 6 By means of a slow intercalation process driven by potential cycling with galvanostatic acceleration, several intercalation phases were distinguished. In order to reach a good efficiency ͑i.e., a high reflectivity/emissivity contrast between the unintercalated and intercalated states relative to the electrochemical input͒ over a wide infrared ͑IR͒ range ͑2-20 m͒, a high crystallinity is required for WO 3 •H 2 O.…”
Section: Introductionmentioning
confidence: 99%
“…Its optical properties in the infrared domain have been investigated in various forms, thin films or powders [12,13], incorporated in rigid or flexible devices [8,9], pointing out the increase in the reflectance modulation for well-crystallised material. Furthermore, Bessière et al [6] reported the key role played by the powder morphology as higher contrasts in reflectance were obtained for large platelet-shaped grains as compared to small parallelepiped ones for WO 3 H 2 O. Higher reflectance modulation was also determined by Hutchins et al [12] for high-temperature, sputtered, crystallised WO 3 films as compared to amorphous ones.…”
Section: Introductionmentioning
confidence: 88%
“…Since then, a few applications including helmet visors or glasses have been reported whereas the most challenging one remains the development of smart windows for use in building and automobile [2,4]. Until recently, most of the applications were turned towards the visible region whereas the IR domain is much less addressed [5][6][7][8][9][10]. In the defence area, the preparation of coatings for vehicles and persons, which would be able to blend into their surrounding and, therefore, become invisible to an infrared camera, is highly desirable [11].…”
Section: Introductionmentioning
confidence: 99%